The possibility of having healthy and hygienic furniture - Jorquera, Daniela; Brancoli , Bernardita (Base Diseño e Innovación, 2015)
The melamine board with antimicrobial copper protection is a unique product in the world and an innovation 100% made in chile. It was developed by Arauco and it is the most effective in the market in the elimination of bacteria, fungi, and mold, thus providing hygiene and care to people wherever it is used.